Effect of Allelopathy from Methanolic Extract of Broadleaf Weeds (Ageratum conyzoides and Borreria alata) on the Viability of Soybean Seeds (Glycine max L.) - Karim Kilkoda, Abdul; Subkhan Mahulette, Asri; Leonard Madubun, Elia (Department of Agronomy and Horticulture, IPB University, 2023)
The experiment aimed to investigate the allelopathic effects of active compounds present in broadleaf weeds Ageratum conyzoides and Borreria alata. The study also sought to assess the viability of various seed varieties grown using allelopathic extracts from these weeds, varying in concentrations of tannins and phenols. The research findings revealed that methanol extracts exhibited potent allelopathic properties, inhibiting germination, radicle and hypocotyl growth, as well as reducing the germination rate of soybean seeds. B. alata weed extracts demonstrated lower allelopathy than A. conyzoides, suggesting a possible alteration in the active compounds (allelochemicals) present due to a reforming process. Extracts from both A. conyzoides and B. alata weeds inhibited root length, hypocotyl growth, and germination across a range of concentrations, from low (10% v/v) to high (30% v/v).